A crooked line : from cultural history to the history of society - Eley, Geoff, 1949- (University of Michigan Press, 2005)
"Eley brilliantly probes transformations in the historians' craft over the past four decades. I found A Crooked Line engrossing, insightful, and inspiring."--Lizabeth Cohen, author of A Consumers' Republic " A Crooked Line brilliantly captures the most significant shifts in the landscape of historical scholarship that have occurred in the last four decades. Part personal history, part insightful analysis of key methodological and theoretical historiographical tendencies since the late 1960s, always thoughtful and provocative, Eley's book shows us why history matters to him and why it should also matter to us."--Robert Moeller, University of California, Irvine "Part genealogy, part diagnosis, part memoir, Eley's account of the histories of social and cultural history is a tour de force."--Antoinette Burton, Professor of History and Catherine C. and Bruce A. Bastian Professor of Global and Transnational Studies, University of Illinois "Eley's reflections on the changing landscape of academic history in the last forty years will interest and benefit all students of the discipline. Both a native informant and an analyst in this account, Eley combines the two roles superbly to produce one of most engaging and compelling narratives of the recent history of History."--Dipesh Chakrabarty, author of Provincializing Europe Using his own intellectual biography as a narrative device, Geoff Eley tracks the evolution of historical understanding in our time from social history through the so-called "cultural turn," and back again to a broad history of society. A gifted writer, Eley carefully winnows unique experiences from the universal, and uses the interplay of the two to draw the reader toward an organic understanding of how historical thinking (particularly the work of European historians) has evolved under the influence of new ideas. His work situates history within History, and offers students, scholars, and general readers alike a richly detailed, readable guide to the enduring value of historical ideas. Geoff Eley is Professor of History at the University of Michigan